PENGARUH MEDIA EXPOSURE, KINERJA LINGKUNGAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP CARBON EMISSION DISCLOSURE - Alfiani, Annisa Dewi; Damayanti, Riska (LPPM Universitas Putera Batam, 2025)
This study aims to determine the effect of Media Exposure on Carbon Emission Disclosure, Environmental Performance on Carbon Emission Disclosure, Company Growth on Carbon Emission Disclosure This type of research is quantitative research with an associative approach. The population in this study are LQ45 index companies listed on the Indonesia Stock Exchange in 2019-2023 by taking Sustainability Report and Annual Report for the 2019-2023 period using purposive sampling. The sample of this study is LQ45 companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. The population used in this study were 65 companies with a selected sample of 20 companies with a total of 100 data observations. This study uses four variables, namely Media Exposure, Environmental Performance, and Company Growth as independent variables while the dependent variable is Carbon Emission Disclodure. The test used is panel data regression analysis using the Eviews 12 program. The results of this study indicate that the Media Exposure and company growth variables have no effect on Carbon Emission Disclosure, the results of this study indicate that the Environmental Performance variable has an effect on Carbon Emission Disclosure. Simultaneously, the results of this study indicate that Media Exposure, Environmental Performance, and Company Growth together have an effect on Carbon Emission Disclosure.